Competency-Based Medical Education: Considering Its Past, Present, and a Post–COVID-19 Era. (23rd February 2022) - Ryan, Michael S.; Holmboe, Eric S.; Chandra, Subani
Abstract : Advancement toward competency-based medical education (CBME) has been hindered by inertia and a myriad of implementation challenges, including those associated with assessment of competency, accreditation/regulation, and logistical considerations. The COVID-19 pandemic disrupted medical education at every level. Time-in-training sometimes was shortened or significantly altered and there were reductions in the number and variety of clinical exposures. These and other unanticipated changes to existing models highlighted the need to advance the core principles of CBME. This manuscript describes the impact of COVID-19 on the ongoing transition to CBME, including the effects on training, curricular, and assessment processes for medical school and graduate medical education programs. The authors outline consequences of the COVID-19 disruption on learner training and assessment of competency, such as conversion to virtual learning modalities in medical school, redeployment of residents within health systems, and early graduation of trainees based on achievement of competency. Finally, the authors reflect on what the COVID-19 pandemic taught them about realization of CBME as the medical education community looks forward to a postpandemic future.